Far-infrared spectrally selective LiTaO3 and AlN pyroelectric detectors using resonant subwavelength metal surface structures. (September 2020) - Arose, Christopher; Terracciano, Anthony C.; Peale, Robert E.; Gonzalez, Francisco Javier; Loparo, Zachary; Cetnar, John; Vasu, Subith S.
Abstract: Plasmonic near-perfect absorbers, comprising metal films with a periodic array of subwavelength openings, were deposited on the surface of pyroelectric materials to create wavelength-selective far-infrared detectors. The detectors fabricated and investigated were based on one of two pyroelectric materials: (i) z-cut monocrystalline lithium tantalate (LiTaO3 ) wafers or, (ii) reactively sputtered aluminum nitride (AlN), with absorbers fabricated by contact photolithography. Spectrally selective absorption resonances were demonstrated by Fourier-transform spectroscopy. Spectrally-selective photoresponse was demonstrated with a tunable THz backward wave oscillator. Responsivity was estimated using a black body source to be ∼ 1 mV/W for AlN samples and ∼ 100 mV/W for LiTaO3 samples. Most similar work has focused on detectors for mid-wave and long-wave infrared spectral regions. Our focus on THz wavelengths beyond 20 μm is motivated by specific security and contraband sensing applications.